THE ROLE AND IMPORTANCE OF MODERN TECHNOLOGIES IN FINE ARTS - Yunusaliyev Muhammadqodir Tadjimatovich (Modern American Journals, 2025)
This article examines the role and importance of modern technologies in the field of fine arts. The ongoing technological advancements, including the use of graphic tablets, 3D modeling, virtual and augmented reality, and artificial intelligence, are revolutionizing creative processes and expanding the expressive capacities of contemporary artists. The paper highlights how these innovations impact not only artistic production but also education, marketing, and cultural exchange. It is argued that mastery of digital tools has become essential for today’s artists, influencing the evolution of the global art market and fostering new forms of cultural interaction. The article also considers the implications for art education and emphasizes the dynamic convergence of art and technology in shaping the future of the creative industries.
Keywords: Fine arts, modern technologies, digital art, artificial intelligence, virtual reality, augmented reality, 3D modeling, art education, NFT, global art market, cultural integration.